Peran Da'i Kamtibmas dalam Pencegahan Radikalisme di Polres Cirebon Kota - Alif Komaldi (Advances in Police Science Research Journal, 2019)
Since 2015, Cirebon has been declared a red zone in the development of radicalism based on Islam. This is evidenced by the development of mass organizations that use Islamic radicalism such as Jemaah Anshorud Tauhid (JAT), Jamaah Ansharusy Syariah (JAS) and Majelis Mujahidin Indonesia (MMI). The number of members of this mass organization is increasingly, causing Cirebon society feel worried about the security conditions in their neighbourhood. The spread of radicalism is increasingly developing following the evolution of technology, namely using social media as a means that are considered effective. This becomes the concentration of Da'i Kamtibmas Cirebon City Police who is considered to have a role in the prevention of radical understanding. The ability of his religious knowledge can help in the prevention of radical understanding as a form of maintaining security and order in the city of Cirebon. This study aims to describe and analyse the efforts and factors that hinder Da’i Kamtibas efforts in preventing radicalism in the Polres Cirebon Kota area. Research location in Polres Cirebon Kota with a focus on Da’i Kamtibmas. This study use qualitative methods with the type of field research. With data collection techniques using interviews, observation, and study documents. This research uses role theory, management theory (management tools), and motivation theory, as well as the concept of community policing, and the Da’i Kamtibmas concept. The role of Da’i Kamtibmas in efforts to prevent radicalism in Polres Cirebon Kota is analysed from role theory, namely people who play a role (as actors and targets), behavior in roles (expectations about roles, norms, behaviour manifestations in norms, judgements and sanctions), position and behavior of people in roles, relationships of people and behavior (criteria of similarity, degrees of interdependence, a combination of similarity criteria and degrees of interdependence, a combination of similarity criteria and degrees of interdependence. In the implementation of the prevention of understanding of radicalism by Da’i Kamtibmas found inhibiting factors which are understanding of radicalism by Da’i Kamtibmas found inhibiting factors which are divided into 2, that is internal factors and external factors. Internal factors included human resources, budget, facilities and infrastructure, and the methods used by Da’i Kamtibmas. External factors included the culture of Cirebon society, lack of embrance from FKPM (Forum Kemitraan Polisi dan Masyarakat) and Islamic mass organizations, the existence of Da’i Kamtibmas in Cirebon society.